Alat Bukti Mata Uang Elektronik Pada Proses Penyidikan Dalam Rangka Pembaharuan Hukum Terhadap Tindak Pidana Pencucian Uang - Budiman, Arief; Rusmiati, Elis; Rukmini, Mien (Universitas Medan Area, 2025)
This study aims to examine the legality and function of electronic currency evidence in Money Laundering Crimes. Existing laws that regulate electronic evidence also do not provide a clear understanding of whether this electronic currency evidence is evidence that can stand alone or is included in electronic evidence that has been previously regulated. The problem is focused on Electronic Currency Evidence which is a new form of evidence whose existence has not been explicitly and clearly regulated in the Criminal Procedure Code, ITE and the Money Laundering Crime Law. In order to approach this problem, a theoretical reference is used from the Legal Certainty Theory. The research method used in this study is normative juridical. Data were collected through literature and field studies, and data collection tools were document studies and interviews and analyzed descriptively qualitatively. The results of the study show that the existence of Electronic Currency has not been explicitly recognized in laws and regulations, although electronic evidence has been recognized in various regulations in Indonesia.